Adaptability of Wheat Genotypes under Multi-environment Trials for Northern Hills Zone - Verma, Ajay; Chatrath, R.; Singh, G. P. (International Journal of Bio-resource and Stress Management, 2020)
Adaptability of wheat genotypes viewed by mixed model together with factor analytic under restricted irrigated late sown trials for the Northern Hills Zone of the country. Analytic measures marked VL892, VL3010 & HS627 as of high yield and better adaptability across major locations of this zone while VL3011 and VL3012 of specific adaptations as per year 2015-16. Biplot analysis expressed stable yield of HS625, HS490 and HPW433 genotypes. Kalimpong and Dhaulakuan, would be suitable environments for stable yield of genotypes while Malan, Imphal and Bajura observed as larger contributor to the G x E interactions. HPW433 had specific adaptations to Kalimpong, Shimla and Dhaulakuan while HS626 for Imphal and Bajura, whereas HS625 identified for Malan. Wheat genotypes HS490, HS660 andVL 3017 had expressed high yield and better adaptability as compared to VL892, UP3017during second year (2017-18) of study.HPW495, VL3016 and HS660 genotypes as positioned near the origin would be of stable nature as compared to HS490, HS661, VL892 and UP3017 had maintained distance from origin in biplot analysis. VL3017 had specific adaptations to Imphal, Malan and Bajura while VL3018 would be for Una, Almora and Dhaulakaun whereas HS662 identified for Shimla, Majhera and Kalimpong. Environments Una with Almora and Dhaulakuan, Bajurawith Imphal and Malan, Shimla with Majhera and Kalimpong would show similar performance of genotypes as acute angle observed among environment rays.